2012
DOI: 10.4149/bll_2012_161
|View full text |Cite
|
Sign up to set email alerts
|

Histological composition of lumbar disc herniations related to the type of herniation and to the age

Abstract: Abstract:Objectives: To compare the data for histologic composition of the herniated disc material between different types of disc herniations and between patients of different age. Background: Lots of studies have investigated the histologic composition of disc herniations. Few studies have examined the presence of granulation tissue related to the type of herniations and age of the subjects. Methods: 120 patients divided in to two age groups underwent MR imaging before microsurgical removal of the herniation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…The number of patients with CDH and LDH increased with age for both men and women. Generally, it is known that DH occurrence increases with age [ 16 , 17 , 18 ]. However, Jordon reported that the number of examinees was the highest for those aged 30–59 years [ 1 ], while Ma et al revealed that the number of patients decreased for those aged ≥60 years [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients with CDH and LDH increased with age for both men and women. Generally, it is known that DH occurrence increases with age [ 16 , 17 , 18 ]. However, Jordon reported that the number of examinees was the highest for those aged 30–59 years [ 1 ], while Ma et al revealed that the number of patients decreased for those aged ≥60 years [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Degenerative changes in the disc and the surrounding neural structures are indeed very common and we can take note of them from the second decade of life. However, structural changes in the disc do not have to signify occurrence of radical clinical symptoms (Matveeva et al, 2012;Bendíková, 2020). Recurrent increase in intradiscal pressure caused by pathological loading of the spine during ADL results in increase in pressure exerted on neural structures contained in the dural bag.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for annular enhancement with the bull's eye sign may be related to vascularization of lumbar disc herniation and formation of granulation tissue [16]. Matveeva et al [17] compared lumbar intervertebral discs from 120 patients with lumbar disc herniation and found that 29% of prolapsed lumbar intervertebral discs had new blood vessels and granulation tissue. In patients with giant lumbar intervertebral disc protrusion, [18].…”
Section: Discussionmentioning
confidence: 99%